2011
DOI: 10.1111/j.1440-0960.2010.00723.x
|View full text |Cite
|
Sign up to set email alerts
|

Thirty-five units of botulinum toxin type A for treatment of axillary hyperhidrosis in female patients

Abstract: We present a retrospective audit on efficacy and impact of 35 units of botulinum toxin type A per axilla on quality of life in female patients with axillary hyperhidrosis. This audit shows that 35 units of botulinum toxin type A is a reasonable starting dose and could significantly improve patients' quality of life and reduce the cost of treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…A number of trials found evidence that the injection of 50 units (U) of BoNT-A per axilla is effective in IH [18][19][20][21][22]. Marcella et al observed that 35U per axilla can be effective and appreciated in female patients with moderate hyperhidrosis, suggesting the possibility of a tailored treatment [24]. Based on these results, an established level of evidence (Level A) exists only for BoNT-A treatment of idiopatic axillary hyperhidrosis [10].…”
Section: Resultsmentioning
confidence: 99%
“…A number of trials found evidence that the injection of 50 units (U) of BoNT-A per axilla is effective in IH [18][19][20][21][22]. Marcella et al observed that 35U per axilla can be effective and appreciated in female patients with moderate hyperhidrosis, suggesting the possibility of a tailored treatment [24]. Based on these results, an established level of evidence (Level A) exists only for BoNT-A treatment of idiopatic axillary hyperhidrosis [10].…”
Section: Resultsmentioning
confidence: 99%
“…Studies that were found to use the HDSS tool were conducted globally, including the USA and Canada (n = 21 21,27,29,52,77,107,108,139,159,160,164,175,176,179,180,208,209,218,225,226,229 ), Spain (n = 6 167,207,210,224,230,231 ), the UK (n = 5 91,97,125,222,232 ), Germany (n = 5 2,131,145,161,227 ), Italy (n = 5 102,106, 136,214,223 ), France (n = 3 59,61,211 ), South Korea (n = 3 51,171,174 ), Australia (n = 2 53,221 ), Egypt (n = 2 213,219 ), Iran (n = 2 28,220 ), the Netherlands (n = 2 ...…”
Section: Hyperhidrosis Disease Severity Scalementioning
confidence: 99%
“…The DLQI was used in studies to measure quality of life on various areas of the body; studies of axillary sweating combined with other parts of the body, such as palms or feet, were most common (n = 26 54,56,69,77,101,103,106,107,114,[119][120][121]139,147,158,170,173,176,214,221,223,263,266,273,274 ). Studies were identified of the palm or palm and foot combined (n = 11 61,128,208,222,230,264,265,[269][270][271][272] ) and of other combinations including the face, palm and/or foot or generalised hyperhidrosis (n = 11 116,117,210,217,227,232,261,262,267,268,275 ).…”
Section: Review Of Quality-of-life Measures/toolsmentioning
confidence: 99%